Hubungan Kualitas Pelayanan dan Citra Perusahaan terhadap Kepuasan Pelanggan Beras Merah pada Perusahaan Daerah Dharma Santika di Kabupaten Tabanan - UDAYANA, I PUTU AGUS ANDIKA; YUDHARI, DEWA AYU SRI; ARTINI, NI WAYAN PUTU (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.13, No.2, Desember 2024, 2024)
The Relationship between Service Quality and Corporate Image on Red Rice Customer Satisfaction at Dharma Santhika Regional Company in Tabanan Regency.  Dharma Santika Regional Companies are companies that in the majority empower regional potentials that are based on small-scale people's economic activities, develop superior and trusted regional companies in the agricultural business sector (in a broad sense), tourism, trade and other services are managed professionally based on strong commercial principles through strong and modern management or management. Public awareness of the fulfillment of balanced nutrition creates an opportunity for the rice market, especially brown rice because of its abundant nutritional content. This study aims to examine the relationship between service quality and corporate image on red rice customer satisfaction at the regional company Dharma Santika. The sample of this research was 35 respondents who were determined by random sampling method. The types of research data are qualitative and quantitative data. Data collection methods are observation, interviews with questionnaires. The data analysis used is multiple linear regression analysis. The results of the regression analysis in this study indicate that there is a real and significant relationship between service quality and corporate image variables on red rice customer satisfaction (H1 and H2 are accepted) which shows a positive correlation value. This means that the better the quality of service provided and the corporate image created, the more red rice customer satisfaction will be. For the company, it is necessary to maintain the image of a company that is already good, and even improve it by holding social activities such as holding charity for people in need. For Dharma Santika Regional Companies, it is necessary to improve the quality of resources in order to provide maximum service so as to give a good impression to customers in negotiating and transacting.